From two competing oscillators to one coupled-clock pacemaker cell system - Yaniv, Yael; Lakatta, Edward G.; Maltsev, Victor A. (Frontiers in Physiology, 2015)
At the beginning of this century, debates regarding “what are the main control mechanisms that ignite the action potential (AP) in heart pacemaker cells” dominated the electrophysiology field. The original theory which prevailed for over 50 years had advocated that the ensemble of surface membrane ion channels (i.e., “M clock”) is sufficient to ignite rhythmic APs. However, more recent experimental evidence in a variety of mammals has shown that the sarcoplasmic reticulum (SR) acts as a “Ca2+ clock” rhythmically discharges diastolic local Ca2+ releases (LCRs) beneath the cell surface membrane. LCRs activate an inward current (likely that of the Na+/Ca2+ exchanger) that prompts the surface membrane “M clock” to ignite an AP. Theoretical and experimental evidence has mounted to indicate that this clock “crosstalk” operates on a beat-to-beat basis and determines both the AP firing rate and rhythm. Our review is focused on the evolution of experimental definition and numerical modeling of the coupled-clock concept, on how mechanisms intrinsic to pacemaker cell determine both the heart rate and rhythm, and on future directions to develop further the coupled-clock pacemaker cell concept.